A multi-scale daily SPEI dataset for drought characterization at observation stations over mainland China from 1961 to 2018 - Wang, Qianfeng; Zeng, Jingyu; Qi, Junyu; Zhang, Xuesong; Zeng, Yue; Shui, Wei; Xu, Zhanghua; Zhang, Rongrong; Wu, Xiaoping; Cong, Jiang (Earth system science data, 2021)
The monthly standardized precipitation evapotranspiration index (SPEI) can be used to monitor and assess drought characteristics with 1-month or longer drought duration. Based on data from 1961 to 2018 at 427 meteorological stations across mainland China, we developed a daily SPEI dataset to overcome the shortcoming of the coarse temporal scale of monthly SPEI. Our dataset not only can be used to identify the start and end dates of drought events, but also can be used to investigate the meteorological, agricultural, hydrological, and socioeconomic droughts with a different timescales. In the present study, the SPEI data with 3-month (about 90 d) timescale were taken as a demonstration example to analyze spatial distribution and temporal changes in drought conditions for mainland China. The SPEI data with a 3-month (about 90 d) timescale showed no obvious intensifying trends in terms of severity, duration, and frequency of drought events from 1961 to 2018. Our drought dataset serves as a unique resource with daily resolution to a variety of research communities including meteorology, geography, and natural hazard studies. The daily SPEI dataset developed is free, open, and publicly available from this study. The dataset with daily SPEI is publicly available via the figshare portal (Wang et al., 2020c), with https://doi.org/10.6084/m9.figshare.12568280.Highlights. A multi-scale daily SPEI dataset was developed across mainland China from 1961 to 2018. The daily SPEI dataset can be used to identify the start and end days of the drought event. The developed daily SPEI dataset in this study is free, open, and publicly available.